(untitled) - Jones, Michael J. (Hoboken, N.J., 2006)
When Steve Sanghi took over as CEO of Microchip Technology in 1990, the company was losing money, its technology was outmoded, and its employees lacked morale. Sanghi, still president and CEO of the company, and Jones, former president of human resources at Microchip, describe how they designed and implemented a model for reform of the entire company.
Keywords: Microchip Technology, Inc.,Semiconductor industry,Organizational effectiveness,Corporate culture,Industrial management; Management,Management; United States